NOOSPHERIC PERSONAL DEVELOPMENT IN CONDITIONS OF TRANSITION PERIOD - Саєнко, Тетяна Василівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article substantiates psychological and pedagogical means of constructing personal plans, goals, full, happy creative life. It was found out that in the conditions of technical universities the main attention is paid to narrow professional training, and in the same period students have the most auspicious time for formation of the dream goal, own well-being, construction of the theory of successful being, strategy of the new person of the XXI century in the transitional conditions of our society and all mankind. The latter is characterized by the recognition of life, human health, environmental benefits as priority universal values, the preservation of which is possible under the change of anthropocentric thinking to eco-centric, the transition to a noosphere system of education and upbringing. Methods of system-structural modeling and eniological diagnostics of efficiency of human self-organization, use of subtle energies for own harmonious development, disclosure of spirituality in interpretation of the world, its challenges are applied, because the worldview reflects the degree of our adequacy to the surrounding reality, and it is rapidly degrading today, which is an indicator of inadequate worldview, reduced moral and ethical potential, the disappearance of the concepts of honor, conscience, responsibility, weakening the influence of education, science and culture. Modern scientific approaches to worldview, conditions of current ecological safety are characterized. First, people should be aware of their actions and processes around to understand their role on the planet, the movement of their energy flows. They should to have an idea of the patterns that operate in the body to consciously manage them to heal, rejuvenate, prolong life. The moral principles and factors of ecological culture, which form the internal basis of ecological safety, noospherogenesis, and sustainable noosphere development in general, are determined. An algorithm for changing the old model of behavior to understand the new one, which includes personal integrity, decency, control, is proposed. The expediency of transforming the system of upbringing, education, thinking of people, especially young people, to anticipate and predict the future has been experimentally proved; confirmed the role of environmental education, noosphere education for the conscious implementation of the provisions of the Code of New Civilization, where it is essential to understand the ecology of the soul and the inner world of man